AN ANALYSIS OF CODE SWITCHING IN ’SUPERNOVA: KSATRIA, PUTRI DAN BINTANG JATUH’ NOVEL BY DEWI LESTARI - Choirotun Nisa & Mujiono (JURNAL ILMIAH BAHASA DAN SASTRA, 2014)
English is a tool used for global communication in this era, when bilinguals switch from one language to another in clause or sentence level that is called code switching. It appears not only in daily communication but also in fiction-written materials. This study was undertaken in a fiction-written material named novel, the researcher chose SUPERNOVA: Ksatria, Putri dan Bintang jatuh” novel by Dewi Lestari as the object. The study was aimed to investigate the code switching produced by the characters. This study used descriptive qualitative approach because the researcher just wanted to know and describe code-switching produced. The research instruments were; researcher, documentation and observation. The result and analysis of the study showed the details of code-switching used. There were 3 types and 6 functions of code switching from the total 21 switches which were pronounced by the characters. The three types were inter-sentential, metaphorical and tag switching. The result showed that the most dominant type was inter-sentential switching. Therefore, the six code switching functions that were found; addressee specification, interference, interjection, intimacy, reiteration and quotation.